Fill up the HR gaps to protect employee satisfaction in Sketch Engineers & Architects Limited - Yasmin, Imrana (BRAC University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2018.